PENGUKURAN KINERJA SDM METODE HUMAN RESOURCES SCORECARD SEBAGAI UPAYA OPTIMALISASI KINERJA ORGANISASI - S, Dwi Ermayanti (Fakultas Ekonomi, UIN Maliki Malang, 2016)
KSP Sejahtera Jatim is one of the cooperatives engaged in saving and loan. As a factor determinesthe attainment of the objectives of the company is employee performance. During this time, KSP SejahteraJatim has being improved the quality of human resources, only measuring soft skill employee performance andsubjectively. The Company has never made the measurement of employee performance as a whole so it isunknown any factors have not been identified and has not been achieved in forming the better quality ofemployee performance. Human Resources Scorecard is a performance measurement system of human resourcethat linked person-strategy-performance to produce a superior company. Human Resources Scorecard describesvision, mission, and human resources strategy into action a measurable contribution. The measurement ofhuman resources performance considering business units from four perspectives are financial perspective,customer perspective, internal business process perspective, learning and growth perspective. Each perspectivewithin Scorecard Human resources method is applied by Analytical Hierarchy process method.